A Novel Mutation in Aspartoacylase Gene; Canavan Disease - ASHRAFI, Mahmoodreza; TAVASOLI, Alireza; KATIBEH, Pegah; ARYANI, Omid; VAFAEE-SHAHI, Mohammad (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Ashrafi MR, Tavasoli AR, Katibeh P, Aryani O, Vafaee-Shahi M. A Novel Mutation In Aspartoacylase Gene; Canavan Disease. Iran J Child Neurol. Autumn 2015; 9(4): 54-57. Abstract Objective Canavan disease (CD) is a type of vacuolating leukodystrophy with autosomal recessive inheritance. Aspartoacylase deficiency results in decrease of myelin biosynthesis, dysmyelination and brain edema. Although CD is a very common in Ashkenazi Jews patients, several cases have been reported from non- Jewish population. This report is based on a homozygous C.202G>A mutation in the ASPA gene identified from an Iranian patient. To our knowledge, this type of mutation has not been reported in non-Jewish population in the literature.